Coexistence of Epilepsy and Psychogenic Nonepileptic Seizures; a Faceless Menace Underlying Pseudointractability - Koç, Güray; Bek, Semai; Gökçil, Zeki (My University, 2019)
Psychogenic nonepileptic seizures (PNES) may be evaluated as epileptic seizures (ES). Moreover, PNES may be accompanied by ES and might be the cause of resistance to antiepileptic drug (AED) in patients with ES which can be defined as pseudoresistance. We aimed to evaluate the rate of PNES and comorbidity of PNES and ES in our database as well as evaluating the prognosis in these patients. We retrospectively evaluated the records of all patients who were admitted to the epilepsy center between January 1, 2007, and March 31, 2015. Medical record review included outpatient clinic notes, neurological findings, video-EEG monitorization reports, home videos of patients, routine EEG reports, brain images, and follow-up of patients. A total of 4247 patients were evaluated and 114 of these patients had PNES. There were 65 patients with PNES only and 49 patients with PNES/ES. Patients with PNES/ES had a longer duration of diagnosis than patients with PNES (p<0.001). Psychiatric treatment was recommended to all, 105 (92.1%) of them had accepted to go under treatment but only 16 (18%) of them took benefit from treatment. Once the patient had epilepsy, all spells were usually considered as epileptic seizures and dosage and number of AED treatment was increased because it was considered as drug resistant epilepsy. We found that suspicion about PNES in patients with intractable epilepsy is helpful to make the right diagnosis and treatment. The clinician who is interested in patients with epilepsy should always keep PNES in mind.
Keywords: Nörolojik Bilimler; Psikiyatri